DOSE-ESCALATED RADIOTHERAPY FOR HIGH-RISK PROSTATE CANCER: OUTCOMES IN MODERN ERA WITH SHORT-TERM ANDROGEN DEPRIVATION THERAPY - Liauw, Stanley L. (2009)
PURPOSE: Randomized data have supported the use of long-term androgen deprivation therapy (ADT) combined with radiotherapy (RT) for men with high-risk prostate cancer. The present study reviewed the outcomes of intermediate- and high-risk men treated with RT and short-term ADT. MATERIALS AND METHODS: A total of 184 men with any single risk factor of prostate-specific antigen ≥10 ng/mL, clinical Stage T2b or greater, or Gleason score ≥7 were treated with primary external beam RT for nonmetastatic adenocarcinoma of the prostate. The median radiation dose was 74 Gy; 55% were treated with intensity-modulated RT. All patients received ADT for 1 to 6 months (median, 4), consisting of a gonadotropin-releasing hormone analog. Univariate and multivariable analyses were performed for risk factors, including T stage, Gleason score, radiation dose, and prostate-specific antigen level. RESULTS: With a median follow-up of 51 months, the 4-year freedom from biochemical failure (FFBF) using the nadir plus 2 ng/mL definition was 83% for all patients. Clinical Stage T3 disease was the only variable tested associated with FFBF on univariate (4-year FFBF rate, 46% vs. 87% for Stage T1-T2c disease; p = .0303) and multivariable analysis (hazard ratio, 3.9; p = .0016). On a subset analysis of high-risk patients (National Comprehensive Cancer Network criteria), those with clinical Stage T3 disease (4-year FFBF rate, 46% vs. 80%; p = .0303) and a radiation dose <74 Gy (4-year FFBF rate, 64% vs. 80%) had a poorer outcome on univariate analysis. However, clinical Stage T3 disease and radiation dose were not significant on multivariable analysis, although a statistical multivariable trend was seen for both (p = .0650 and p = .0597, respectively). CONCLUSION: Short-term ADT and RT might be acceptable for men with intermediate- and high-risk prostate cancer, especially for clinically localized disease treated with doses of ≥74 Gy.